1997
DOI: 10.1080/0042098976050
|View full text |Cite
|
Sign up to set email alerts
|

Space to Grow Old In: The Availability of Public Spaces for Elderly Persons in Singapore

Abstract: Using a political economy approach, this paper examines the provision of facilities and services for elderly persons in urban Singapore. It posits that policies concerning this group are socially constructed and that ageist notions affect the spatial forms created for meeting the health, housing and social needs of older people. It emphasises the signi® cance of subjectivity in the environmental strategies of older persons and investigates the extent to which state provisions incorporate the concept of persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…For example, participants recruited from street interviews indicated the importance of pavilions and public parks. This aligns with the previous study conducted by Teo (1997) on 148 elderly living in Bukit Merah and Tampines, which also showed that elderly meet up not only at structured social spaces like SACs, but also at informal public spaces such as coffeeshops and void decks. In addition, male participants, who were mostly recruited through street interviews, perceived social cohesiveness significantly higher than female participants.…”
Section: Provision and Planning Of Formal And Informal Social Spacessupporting
confidence: 91%
See 1 more Smart Citation
“…For example, participants recruited from street interviews indicated the importance of pavilions and public parks. This aligns with the previous study conducted by Teo (1997) on 148 elderly living in Bukit Merah and Tampines, which also showed that elderly meet up not only at structured social spaces like SACs, but also at informal public spaces such as coffeeshops and void decks. In addition, male participants, who were mostly recruited through street interviews, perceived social cohesiveness significantly higher than female participants.…”
Section: Provision and Planning Of Formal And Informal Social Spacessupporting
confidence: 91%
“…This area of study has largely been unexplored in Singapore's context in recent years. Teo (1997) examined the provision of facilities and services for elderly persons in urban Singapore, and posited that policies concerning this group are socially constructed spatial forms that may not adequately meet their needs, emphasizing the significance of subjectivity in environmental strategies of designing for older people-especially in land-scarce Singapore. In particular, Teo conducted surveys on 148 elderly living in Tampines and Bukit Merah to investigate their use of public space and various designated elderly corners and services provided by the state (e.g., community centers).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rural -urban migration that has followed industrialization in many countries has been well documented; yet there are also important social and cultural geographies of South-East Asia that unsettle neat dichotomies of 'rural' versus 'urban' (McGee 1991;Thompson 2002). The growth of cities and expanded urban regions has spawned new kinds of social and political problematics-from commuting Country reports 139 (Punpuing and Ross 2001) to high-rise 'killer' littering (Bunnell 2002c) to accommodating increasing numbers of elderly people (Teo 1997). Urban life has also enabled new and newly differentiated 'cultures': from ideals of 'womanhood' (Ledgerwood 1996) and sexual lifestyles (Ford and Kittisukathit 1996) to spaces of consumption, whether shopping malls or 'roads for the BMW' (Leaf 1996).…”
Section: Politics Of Urban Changementioning
confidence: 97%
“…Human health has been defined as "a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity" (WHO, 1948). Accordingly, aside from conducive to physical health, urban green space also has a number of psychological benefits (Orsega-Smith et al, 2004;Teo, 1997). The concept of "biophila" suggests that human cannot be separated from nature, and contact with nature is the essence for the psychological well-being (see Kellert and Wilson, 1993).…”
Section: Social Benefits Of Green Spacementioning
confidence: 99%